Days of destruction, days of revolt - Hedges, Chris (Nation Books, 2012)
Camden, New Jersey was once an industrial giant. It employed some 36,000 workers in its shipyards during World War II and built some of the nation's largest warships. It was the home to major industries, from RCA Victor to Campbell's Soup. It was a destination for immigrants and upwardly mobile lower middle class families. Camden now resembles a penal colony. In Days of Destruction, Days of Revolt, Pulitzer Prize winning journalist Chris Hedges and American Book Award winning cartoonist Joe Sacco show how places like Camden, a poster child of postindustrial decay, stand as a warning of what huge pockets of the United States will turn into if we cement in place a permanent underclass.